SYMBOLIC PRODUCTION OF COFFEE-DRINKING: GENEALOGY, PROBLEMATIZATION AND THE CASE OF CORDILLERA COFFEE - Aliya S Peleo (Department of International Relations, Brawijaya University, 2018)
This paper explores the genealogy of coffee-drinking and how it has changed through history with particularly focus on the problematization of coffee as a ‘cultural’ symbol for people in different parts of the World and in different historic periods and locate the contemporary symbolic production of coffee as a ‘development project’ in the case of the Cordillera region in the Philippines. From the first glance, the political economy and culture of coffee-drinking for both consumers and producers in any part of the World at its core is local. However, coffee becomes part of the international politics when populations of different local geographic spaces need to interact with each other to continue their ‘local’ patterns of lifestyle for consumption or production. The international interaction is often expressed through biopolitical hierarchies of interaction between (1) the wealthy populations in the developed countries of Global North with (2) the vulnerable subsistent populations in the underdeveloped countries of Global South. Often these two groups of people have limited knowledge about the context of biopolitical administration of ‘life processes’ in each geographic space. How is this limitation negotiated and processed through symbolic construction of what ‘coffee’ has meant for people through history?